Survival and cause‐specific mortality of elk Cervus canadensis in Kentucky, USA. Issue 1 (18th December 2018) - Slabach, Brittany L.; Hast, John T.; Murphy, Sean M.; Bowling, Willie E.; Crank, R. Daniel; Jenkins, Gabe; Johannsen, Kristina L.; Cox, John J.
Abstract : Wildlife management relies heavily on high quality field data to analyze and predictively model animal population dynamics, evaluate population viability, and ultimately inform management decisions. During 2011–2015, we conducted a study to investigate survival and cause‐specific mortality of male and female elk Cervus canadensis in a harvested population in southeastern Kentucky, USA, which was established via reintroduction a decade prior. Preliminary male elk survival data led state wildlife managers to modify hunting zone boundaries and establish several areas with limited hunter access mid‐way (2013) through our study to attempt to improve male survival and prevent overharvest. Thus, we also investigated the effectiveness of limiting hunter access for improving male elk survival in one of these regulated areas. We captured and radio‐monitored 237 (F91:M146) elk, of which 155 (65.4%) died by the conclusion of our study; harvest‐related deaths were the leading causes of mortality for both sexes (85.2%; 132/155). Estimated mean annual female and male survival rates were 0.67 (95% CI = 0.53–0.81) and 0.57 (95% CI = 0.45–0.71), respectively. Results from Cox proportional hazards regression models indicated that females < 2 years‐of‐age (HR≤2yoa = 3.84, p = 0.004) and males ≥ 5 years‐of‐age (HR5yoa = 1.83, p = 0.01; HR≥6yoa = 2.26, p = 0.004) had significantly higher hazards of dying compared to other sex‐specific age classes. Support also existed for variation in female survival by herd. The establishment of areas that limited hunter access did not affect male elk survival, as estimates were similar pre and post‐implementation. Given the probability of mortality from harvest was consistently much higher for both sexes relative to other causes, we suggest that reducing overall harvest permits likely would be the most effective management action for improving elk survival and reducing the potential of overharvest of this population.